Clinical application of metagenomic next-generation sequencing in non-immunocompromised patients with severe pneumonia supported by veno-venous extracorporeal membrane oxygenation - Li, Xing-Xing; Niu, Cheng-Zhi; Zhao, Yang-Chao; Fu, Guo-Wei; Zhao, Hui; Huang, Ming-Jun; Li, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives This study aims to explore the pathogen-detected effect of mNGS technology and its clinical application in non-immunocompromised patients with severe pneumonia supported by vv-ECMO. Methods A retrospective analysis was conducted on a cohort of 50 non-immunocompromised patients who received vv-ECMO support for severe pneumonia between January 2016 and December 2022. These patients were divided into two groups based on their discharge outcomes: the deterioration group (Group D), which included 31 cases, and the improvement group (Group I), consisting of 19 cases. Baseline characteristics and clinical data were collected and analyzed. Results Among the 50 patients enrolled, Group D exhibited a higher prevalence of male patients (80.6% vs. 52.6%, p < 0.05), more smokers (54.8% vs. 21.1%, p < 0.05), and were older than those in Group I (55.16 ± 16.34 years vs. 42.32 ± 19.65 years, p < 0.05). Out of the 64 samples subjected to mNGS detection, 55 (85.9%) yielded positive results, with a positivity rate of 83.7% (36/43) in Group D and 90.5% (19/21) in Group I. By contrast, the positive rate through traditional culture stood at 64.9% (74/114). Among the 54 samples that underwent both culture and mNGS testing, 23 (42.6%) displayed consistent pathogen identification, 13 (24.1%) exhibited partial consistency, and 18 (33.3%) showed complete inconsistency. Among the last cases with complete inconsistency, 14 (77.8%) were culture-negative, while two (11.1%) were mNGS-negative, and the remaining two (11.1%) presented mismatches. Remarkably, mNGS surpassed traditional culture in pathogen identification (65 strains vs. 23 strains). Within these 65 strains, 56 were found in Group D, 26 in Group I, and 17 were overlapping strains. Interestingly, a diverse array of G+ bacteria, fungi, viruses, and special pathogens were exclusive to Group D. Furthermore, Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae were more prevalent in Group D compared to Group I. Importantly, mNGS prompted antibiotic treatment adjustments in 26 patients (52.0%). Conclusions Compared with the conventional culture, mNGS demonstrated a higher positive rate, and emerges as a promising method for identifying mixed pathogens in non-immunodeficient patients with severe pneumonia supported by vv-ECMO. However, it is crucial to combine the interpretation of mNGS data with clinical information and traditional culture results for a comprehensive assessment.